Bending-resistant data line material and preparation method thereof
By using SEBS, polypropylene, ethylene propylene rubber and thermoplastic polyurethane elastomers in the data line material and adding composite flame retardant, the physical barrier effect of nanotubes and layered structures is used to solve the resistance problem of the data line material during combustion and bending, achieving higher flame retardant and bending resistance.
Patent Information
- Application Number
- CN202411845645.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-25
AI Technical Summary
Existing data cable materials are prone to fire when burning, and have poor resistance during bending, making it difficult to meet safety performance and actual use requirements.
Materials such as SEBS, polypropylene, ethylene propylene ternary rubber and thermoplastic polyurethane elastomers are used, and the physical barrier effect and layered structure of Elosite nanotubes and MXene nanosheets are used to improve flame retardant performance and bending resistance through the addition of composite flame retardant agents.
The flame retardant and bending resistance of data line materials are significantly improved, fire risk is reduced, and wear resistance and mechanical properties of the material are enhanced.
Smart Images

Figure BDA0005189116720000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermoplastic elastomers, and in particular to a bending-resistant data line material and a preparation method thereof. Background Art
[0002] Data cables are an indispensable part of electronic products. They are mainly composed of conductors, insulating materials, and external wire materials. The external wire materials mainly include TPE materials (thermoplastic elastomer materials), PVC materials (polyvinyl chloride materials), and braided nylon materials. When the external wire material is PVC, the data cable is easy to break, has a short life, and has poor bending resistance; when it is braided nylon material, the data cable has poor flame retardancy, is expensive, and has poor safety performance; when TPE material is used as the external wire material, it has excellent elasticity, toughness, and environmental protection, and the material has good durability. Therefore, using TPE material as the external wire material of the data cable has a good application prospect.
[0003] Although TPE material has many advantages as the outer line material of data cables, considering that fires caused by burning of data cables have occurred frequently in recent years, the flame retardancy of the material needs to be further improved, thereby improving the safety performance of the data cables and reducing the occurrence of fires; in addition, considering that there may be many bends during use, the toughness of the material needs to be further improved to meet actual needs. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a bending-resistant data line material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A bending-resistant data cable material comprises the following raw materials in parts by weight: 60-80 parts of SEBS, 10-18 parts of a composite flame retardant, 12-18 parts of polypropylene, 10-20 parts of EPDM rubber, 4-9 parts of a thermoplastic polyurethane elastomer, 8-15 parts of white oil, 0.8-2 parts of an antioxidant, and 1-2 parts of stearic acid;
[0007] The antioxidant is one of antioxidant 1010 or antioxidant 168;
[0008] The composite flame retardant is prepared by the following steps:
[0009] Step A1, melamine and triethylamine are stirred evenly in dichloromethane, O,O-dimethylphosphoryl chloride is slowly added, and stirred at 0-5°C for 1-2h, and then stirred at room temperature for 8-12h, filtered, washed 3-5 times, and redispersed in an equal amount of dichloromethane, and then 2,2-dihydroxymethylpropionic acid, 1-hydroxybenzotriazole and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are added, stirred for reaction for 2-3h, filtered, washed, and dried to obtain a cross-linked intermediate;
[0010] Step A2, mixing the cross-linked intermediate and glyoxylic acid, heating to 90-100° C. and stirring for 30 min, then introducing nitrogen, adding cyclohexane and p-toluenesulfonic acid, and then heating to 135-145° C. to react for 1-2 h, stopping the introduction of nitrogen, and continuing the reaction under vacuum conditions for 1-2 h to obtain a cross-linked product;
[0011] Step A3, under nitrogen conditions, add KH-550 (silane coupling agent) to ethanol and stir for 5-10 minutes, then add MXene nanosheet aqueous solution and stir for 30-50 minutes, adjust the pH to 4-5, react at 30-50° C. for 8-12 hours, centrifuge, wash and dry to obtain amino MXene nanosheets;
[0012] Step A4, the halloysite nanotubes, polyvinyl alcohol and deionized water are mixed and stirred evenly, the temperature is raised to 90-100°C, the temperature is kept for reaction for 40-60min, and then the temperature is lowered to 50-60°C, silicone oil and sodium dodecyl sulfate are added and stirred for 1-2h, the cross-linked product and 10wt% hydrochloric acid are added and stirred for 0.5-1.5h, centrifuged, washed, and the product is collected, and the amino MXene nanosheet solution is added, the temperature is maintained for reaction for 3-5h, centrifuged, washed, and then 10-15mg / mL sodium cyanoborohydride solution is added for reaction for 2-3h, centrifuged, washed, and dried to obtain a composite flame retardant;
[0013] Further, in step A1, the usage ratio of melamine, triethylamine, dichloromethane, O,O-dimethylphosphoryl chloride, 2,2-dihydroxymethylpropionic acid, 1-hydroxybenzotriazole and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 0.01-0.02 mol: 0.02-0.04 mol: 500 mL: 0.02-0.04 mol: 0.01-0.02 mol: 0.011-0.022 mol: 0.011-0.022 mol;
[0014] Further, in step A2, the usage ratio of the cross-linked intermediate, glyoxylic acid, cyclohexane and p-toluenesulfonic acid is 5-10 g: 1.7-3.4 g: 30-50 mL: 0.1-0.3 g;
[0015] Further, in step A3, the dosage ratio of KH-550, ethanol and MXene nanosheet aqueous solution is 0.5-1 g: 20 mL: 10 mL;
[0016] Furthermore, the MXene nanosheet aqueous solution in step A3 is prepared by the following steps: 3-6 g Ti 3 AlC 2 The powder is dispersed in 50-100 mL of 40% hydrofluoric acid (w / v), stirred in a 30-40°C water bath for 12-24 h, filtered and washed until the filtrate is neutral, then the filter cake is dried and redispersed in 10 mL of deionized water to obtain an aqueous solution of MXene nanosheets;
[0017] Further, in step A4, the usage ratio of halloysite nanotubes, polyvinyl alcohol, deionized water, silicone oil, sodium dodecyl sulfate, cross-linked product, hydrochloric acid, amino MXene nanosheet solution and sodium cyanoborohydride solution is 1.5-2.5 g: 3-5 g: 50 mL: 80-100 mL: 2-4 g: 0.5-1.5 g: 8-16 mL: 20 mL: 5 mL;
[0018] Furthermore, in step A4, the aminated MXene nanosheet solution is prepared by mixing and stirring the aminated MXene nanosheets and deionized water in a dosage ratio of 0.2-0.6 g: 20 mL.
[0019] A method for preparing a bending-resistant data line material comprises the following steps:
[0020] Step S1, weighing raw materials by weight, adding SEBS, polypropylene, EPDM rubber and thermoplastic polyurethane elastomer into a mixer, stirring at a speed of 500-700 rpm, then adding composite flame retardant, white oil, antioxidant and stearic acid, stirring at a speed of 200-400 rpm for 30 minutes to obtain a mixture;
[0021] Step S2, putting the mixed material into a twin-screw extruder, melting and extruding at 180-200° C., and granulating to obtain a bending-resistant data cable material.
[0022] Beneficial effects of the present invention:
[0023] The data line material of the present invention is synthesized by using SEBS, polypropylene and EPDM rubber with excellent bending resistance as main raw materials, and adding various additives to improve the comprehensive performance of the matrix; the introduction of thermoplastic polyurethane elastomer improves the wear resistance and mechanical properties of the matrix; the composite flame retardant uses a combination of organic flame retardant and inorganic flame retardant to comprehensively improve the flame retardant performance of the matrix.
[0024] The data line material of the present invention introduces thermoplastic polyurethane elastomer, which can cooperate with SEBS, polypropylene and EPDM rubber, and utilize its own excellent elasticity and wear resistance to further improve the bending resistance and wear resistance of the substrate.
[0025] The composite flame retardant of the invention first uses melamine as an intermediate, and makes it react with O, O-dimethylphosphoryl chloride and 2, 2-dimethylolpropionic acid to obtain a cross-linked intermediate; then the cross-linked intermediate is reacted with glyoxylic acid to obtain a cross-linked product; then a silane coupling agent is used to modify the surface of the MXene nanosheet to obtain an amino MXene nanosheet; finally, polyvinyl alcohol is used to coat the halloysite nanotube, and the cross-linked product is used as a cross-linking agent to composite the coated nanotube with the MXene nanosheet to obtain the composite flame retardant. The addition of the composite flame retardant improves the flame retardant properties of the matrix. This is because the halloysite nanotubes and MXene nanosheets contained in the composite flame retardant can work synergistically, using their own tubular structure and layered structure to act as a physical barrier in the matrix, construct a "maze" in the matrix, and extend the diffusion path of the gas during the combustion process; the triazine structure and phosphate structure contained in the cross-linked product also have a certain flame retardant effect, further improving the flame retardant properties of the matrix; the polyvinyl alcohol coated on the surface of the halloysite nanotubes can form an expanded carbon layer during the combustion process. This carbon layer not only isolates oxygen, but also acts as a heat insulator, thereby slowing down or terminating the combustion. In addition, the halloysite nanotubes and MXene nanosheets in the composite flame retardant have excellent mechanical properties, which can improve the toughness of the matrix, so that when the matrix is subjected to bending force, it can absorb energy through plastic deformation, thereby reducing the risk of fracture, and further improving the bending resistance of the matrix. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1: The composite flame retardant is prepared by the following steps:
[0028] Step A1, 0.01 mol of melamine and 0.02 mol of triethylamine were stirred evenly in 250 mL of dichloromethane, 0.02 mol of O, O-dimethylphosphoryl chloride was slowly added, and stirred at 0°C for 1 hour, and then stirred at room temperature for 8 hours, filtered, washed 3 times, and redispersed in 250 mL of dichloromethane, and then 0.01 mol of 2,2-dihydroxymethylpropionic acid, 0.011 mol of 1-hydroxybenzotriazole and 0.011 mol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added, stirred for reaction for 2 hours, filtered, washed, and dried to obtain a cross-linked intermediate;
[0029] Step A2, 5 g of the cross-linked intermediate and 1.7 g of glyoxylic acid were mixed, and the mixture was heated to 90° C. and stirred for 30 min, and then nitrogen was introduced, 30 mL of cyclohexane and 0.1 g of p-toluenesulfonic acid were added, and the mixture was heated to 135° C. and reacted for 1 h, and the nitrogen introduction was stopped, and the reaction was continued under vacuum conditions for 1 h to obtain a cross-linked product;
[0030] Step A3, under nitrogen conditions, add 0.5g KH-550 (silane coupling agent) to 20mL ethanol and stir for 5min, then add 10mL MXene nanosheet aqueous solution and stir for 30min, adjust the pH to 4, react at 30°C for 8h, centrifuge, wash and dry to obtain amino MXene nanosheets. The MXene nanosheet aqueous solution is prepared by the following steps: 3g Ti 3 AlC 2 The powder was dispersed in 50 mL of 40% hydrofluoric acid (w / v), stirred in a 30 °C water bath for 12 h, filtered and washed until the filtrate was neutral, then the filter cake was dried and redispersed in 10 mL of deionized water to obtain an aqueous solution of MXene nanosheets;
[0031] Step A4, 1.5g of halloysite nanotubes, 3g of polyvinyl alcohol and 50mL of deionized water were mixed and stirred evenly, the temperature was raised to 90°C, the reaction was kept warm for 40min, and then the temperature was lowered to 50°C, 80mL of silicone oil and 2g of sodium dodecyl sulfate were added and stirred for 1h, 0.5g of the cross-linked product and 8mL of 10wt% hydrochloric acid were added and stirred for 0.5h, centrifuged, washed, and the product was collected, 20mL of the amino MXene nanosheet solution was added, the temperature was maintained for 3h, centrifuged, washed, and then 5mL of 10mg / mL sodium cyanoborohydride solution was added to react for 2h, centrifuged, washed, and dried to obtain a composite flame retardant. The amino MXene nanosheet solution is prepared by mixing and stirring the amino MXene nanosheets and deionized water in a dosage ratio of 0.2g:20mL.
[0032] Example 2: The composite flame retardant is prepared by the following steps:
[0033] Step A1, 0.015 mol of melamine and 0.03 mol of triethylamine were stirred evenly in 250 mL of dichloromethane, 0.03 mol of O, O-dimethylphosphoryl chloride was slowly added, and the mixture was stirred at 3°C for 1.5 h, and then stirred at room temperature for 10 h, filtered, washed 4 times, and redispersed in 250 mL of dichloromethane, and 0.015 mol of 2,2-dihydroxymethylpropionic acid, 0.016 mol of 1-hydroxybenzotriazole and 0.016 mol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added, stirred for reaction for 2.5 h, filtered, washed and dried to obtain a cross-linked intermediate;
[0034] Step A2, 7.5 g of the cross-linked intermediate and 2.6 g of glyoxylic acid were mixed, and the temperature was raised to 95 ° C. and stirred for 30 min, and then nitrogen was introduced, 40 mL of cyclohexane and 0.2 g of p-toluenesulfonic acid were added, and the temperature was raised to 140 ° C. for reaction for 1.5 h, and the nitrogen was stopped, and the reaction was continued under vacuum conditions for 1.5 h to obtain a cross-linked product;
[0035] Step A3, under nitrogen conditions, add 0.75g KH-550 (silane coupling agent) to 20mL ethanol and stir for 7min, then add 10mL MXene nanosheet aqueous solution and stir for 40min, adjust the pH to 4.5, react at 40°C for 10h, centrifuge, wash and dry to obtain amino MXene nanosheets. The MXene nanosheet aqueous solution is prepared by the following steps: 4.5g Ti 3 AlC 2 The powder was dispersed in 80 mL of 40% hydrofluoric acid (w / v), stirred in a 35 °C water bath for 18 h, filtered and washed until the filtrate was neutral, then the filter cake was dried and redispersed in 10 mL of deionized water to obtain an aqueous solution of MXene nanosheets;
[0036] Step A4, 2g of halloysite nanotubes, 4g of polyvinyl alcohol and 50mL of deionized water were mixed and stirred evenly, the temperature was raised to 95°C, the reaction was kept warm for 50min, and then the temperature was lowered to 55°C, 90mL of silicone oil and 3g of sodium dodecyl sulfate were added and stirred for 1.5h, 1g of the cross-linked product and 12mL of 10wt% hydrochloric acid were added and stirred for 1h, centrifuged, washed, and the product was collected, 20mL of the amino MXene nanosheet solution was added, the temperature was maintained for 4h, centrifuged, washed, and then 5mL of 12mg / mL sodium cyanoborohydride solution was added to react for 2.5h, centrifuged, washed, and dried to obtain a composite flame retardant. The amino MXene nanosheet solution is prepared by mixing and stirring the amino MXene nanosheets and deionized water in a dosage ratio of 0.4g:20mL.
[0037] Example 3: The composite flame retardant is prepared by the following steps:
[0038] Step A1, 0.02 mol of melamine and 0.04 mol of triethylamine were stirred evenly in 250 mL of dichloromethane, 0.04 mol of O, O-dimethylphosphoryl chloride was slowly added, and stirred at 5°C for 2 hours, and then stirred at room temperature for 12 hours, filtered, washed 5 times, and redispersed in 250 mL of dichloromethane, and then 0.02 mol of 2,2-dihydroxymethylpropionic acid, 0.022 mol of 1-hydroxybenzotriazole and 0.022 mol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added, stirred and reacted for 3 hours, filtered, washed and dried to obtain a cross-linked intermediate;
[0039] Step A2, 10 g of the cross-linked intermediate and 3.4 g of glyoxylic acid were mixed, and the mixture was heated to 100 ° C. and stirred for 30 min, and then nitrogen was introduced, 50 mL of cyclohexane and 0.3 g of p-toluenesulfonic acid were added, and the mixture was heated to 145 ° C. for reaction for 2 h, and the nitrogen was stopped, and the reaction was continued under vacuum conditions for 2 h to obtain a cross-linked product;
[0040] Step A3, under nitrogen conditions, add 1g KH-550 (silane coupling agent) to 20mL ethanol and stir for 10min, then add 10mL MXene nanosheet aqueous solution and stir for 50min, adjust the pH to 5, react at 50°C for 12h, centrifuge, wash and dry to obtain amino MXene nanosheets. The MXene nanosheet aqueous solution is prepared by the following steps: 6g Ti 3 AlC 2 The powder was dispersed in 100 mL of 40% hydrofluoric acid (w / v), stirred in a 40°C water bath for 24 h, filtered and washed until the filtrate was neutral, then the filter cake was dried and redispersed in 10 mL of deionized water to obtain an aqueous solution of MXene nanosheets;
[0041] Step A4, 2.5g of halloysite nanotubes, 5g of polyvinyl alcohol and 50mL of deionized water were mixed and stirred evenly, the temperature was raised to 100°C, the reaction was kept warm for 60min, and then the temperature was lowered to 60°C, 100mL of silicone oil and 4g of sodium dodecyl sulfate were added and stirred for 2h, 1.5g of the cross-linked product and 16mL of 10wt% hydrochloric acid were added and stirred for 1.5h, centrifuged, washed, and the product was collected, 20mL of the amino MXene nanosheet solution was added, the temperature was maintained for 5h, centrifuged, washed, and then 5mL of 15mg / mL sodium cyanoborohydride solution was added to react for 3h, centrifuged, washed, and dried to obtain a composite flame retardant. The amino MXene nanosheet solution was prepared by mixing and stirring the amino MXene nanosheets and deionized water in a dosage ratio of 0.6g:20mL.
[0042] Embodiment 4: A method for preparing a bending-resistant data line material comprises the following steps:
[0043] 60 parts of SEBS, 10 parts of the composite flame retardant prepared in Example 1, 12 parts of polypropylene, 10 parts of EPDM rubber, 4 parts of thermoplastic polyurethane elastomer, 8 parts of white oil, 1680.8 parts of antioxidant, and 1 part of stearic acid;
[0044] Step S1, weighing raw materials by weight, adding SEBS, polypropylene, EPDM rubber and thermoplastic polyurethane elastomer into a mixer, stirring at a speed of 500 rpm, and then adding the composite flame retardant prepared in Example 1, white oil, antioxidant 168 and stearic acid, stirring at a speed of 200 rpm for 30 minutes to obtain a mixture;
[0045] Step S2, putting the mixed material into a twin-screw extruder, melting and extruding at 180° C., and granulating to obtain a bending-resistant data cable material.
[0046] Embodiment 5: A method for preparing a bending-resistant data line material comprises the following steps:
[0047] SEBS 70 parts, composite flame retardant prepared in Example 2 14 parts, polypropylene 14 parts, EPDM rubber 15 parts, thermoplastic polyurethane elastomer 6 parts, white oil 12 parts, antioxidant 1010 1.5 parts, stearic acid 1.5 parts;
[0048] Step S1, weighing raw materials by weight, adding SEBS, polypropylene, EPDM rubber and thermoplastic polyurethane elastomer into a mixer, stirring at a speed of 600 rpm, and then adding the composite flame retardant prepared in Example 2, white oil, antioxidant 1010 and stearic acid, stirring at a speed of 300 rpm for 30 minutes to obtain a mixture;
[0049] Step S2, putting the mixed material into a twin-screw extruder, melting and extruding at 190° C., and granulating to obtain a bending-resistant data cable material.
[0050] Embodiment 6: A method for preparing a bending-resistant data line material comprises the following steps:
[0051] 80 parts of SEBS, 18 parts of the composite flame retardant prepared in Example 3, 18 parts of polypropylene, 20 parts of EPDM rubber, 9 parts of thermoplastic polyurethane elastomer, 15 parts of white oil, 10102 parts of antioxidant, and 2 parts of stearic acid;
[0052] Step S1, weighing raw materials by weight, adding SEBS, polypropylene, EPDM rubber and thermoplastic polyurethane elastomer into a mixer, stirring at a speed of 700 rpm, and then adding the composite flame retardant, white oil, antioxidant and stearic acid prepared in Example 3, stirring at a speed of 400 rpm for 30 minutes to obtain a mixture;
[0053] Step S2, putting the mixed material into a twin-screw extruder, melting and extruding at 200° C., and granulating to obtain a bending-resistant data cable material.
[0054] Comparative Example 1: This comparative example is a data line material. The difference from Example 6 is that magnesium hydroxide is used instead of the composite flame retardant prepared in Example 3, and the rest is the same.
[0055] Comparative Example 2: This comparative example is a data line material, which differs from Example 6 in that no thermoplastic polyurethane elastomer is added, and the rest are the same.
[0056] The data line materials prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests:
[0057] Flame retardant performance test: refer to ASTMD3801 standard, the test sample size is 125×12.7×3.2mm 3 ;
[0058] Limiting oxygen index test: According to GB / T 2406.2-2009, the test sample size is 130×6.5×3.2mm 3 ;
[0059] Abrasion resistance test: Tested in accordance with GB / T 1689-2014;
[0060] Anti-bending performance test: A 360-degree bending test machine was used to conduct anti-bending performance swing tests on Examples 4-6 and Comparative Examples 1-2, respectively. A weight was added to the data line material as a load, so that the applied force was 5N. A clamping plate R = 10mm swing mechanism was used to swing 180° (90° on both sides of the plumb line), the number of swings was 5000, and the swing rate was 30 times per minute. During the test, a current of 0.5A was required. If no breakage occurred after the test, it was recorded as '0', if breakage or severe cracks occurred, it was recorded as '1', and if slight cracks occurred, it was recorded as '2'.
[0061] Mechanical properties test: The tensile strength and elongation at break of the data cable material are tested according to ASTM D412 "Tensile test methods for vulcanized rubber and thermoplastic elastomers";
[0062] The test results are shown in Table 1:
[0063]
[0064] As can be seen from Table 1, the data cable material prepared by the present invention has excellent flame retardancy, wear resistance, bending resistance and mechanical properties after flame retardancy test, limiting oxygen index test, wear resistance test, bending resistance test and mechanical properties test.
[0065] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A bending-resistant data line material, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of SEBS, 10-18 parts of composite flame retardant, 12-18 parts of polypropylene, 10-20 parts of EPDM rubber, 4-9 parts of thermoplastic polyurethane elastomer, 8-15 parts of white oil, 0.8-2 parts of antioxidant and 1-2 parts of stearic acid; The composite flame retardant is prepared by the following steps: Step A1, melamine and triethylamine are stirred evenly in dichloromethane, O,O-dimethylphosphoryl chloride is slowly added, and stirred at 0-5°C for 1-2h, and then stirred at room temperature for 8-12h, filtered, washed 3-5 times, and redispersed in an equal amount of dichloromethane, and then 2,2-dihydroxymethylpropionic acid, 1-hydroxybenzotriazole and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are added, stirred for reaction for 2-3h, filtered, washed, and dried to obtain a cross-linked intermediate; Step A2, mixing the cross-linked intermediate and glyoxylic acid, heating to 90-100° C. and stirring for 30 min, then introducing nitrogen, adding cyclohexane and p-toluenesulfonic acid, and then heating to 135-145° C. to react for 1-2 h, stopping the introduction of nitrogen, and continuing the reaction under vacuum conditions for 1-2 h to obtain a cross-linked product; Step A3, under nitrogen conditions, add KH-550 to ethanol and stir for 5-10 minutes, then add MXene nanosheet aqueous solution and stir for 30-50 minutes, adjust the pH to 4-5, react at 30-50°C for 8-12 hours, centrifuge, wash and dry to obtain amino MXene nanosheets; Step A4, the halloysite nanotubes, polyvinyl alcohol and deionized water are mixed and stirred evenly, the temperature is raised to 90-100 ° C, the temperature is kept for reaction for 40-60 minutes, and then the temperature is lowered to 50-60 ° C, silicone oil and sodium dodecyl sulfate are added and stirred for 1-2 hours, the cross-linked product and 10wt% hydrochloric acid are added and stirred for 0.5-1.5 hours, centrifuged, washed, and the product is collected, and the amino MXene nanosheet solution is added, the temperature is maintained for 3-5 hours, centrifuged, washed, and then 10-15mg / mL sodium cyanoborohydride solution is added to react for 2-3 hours, centrifuged, washed, and dried to obtain a composite flame retardant.
2. The bending-resistant data line material according to claim 1, characterized in that: In step A1, the usage ratio of melamine, triethylamine, dichloromethane, O,O-dimethylphosphoryl chloride, 2,2-dihydroxymethylpropionic acid, 1-hydroxybenzotriazole and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 0.01-0.02 mol: 0.02-0.04 mol: 500 mL: 0.02-0.04 mol: 0.01-0.02 mol: 0.011-0.022 mol: 0.011-0.022 mol.
3. The bending-resistant data line material according to claim 1, characterized in that: In step A2, the usage ratio of the cross-linking intermediate, glyoxylic acid, cyclohexane and p-toluenesulfonic acid is 5-10 g: 1.7-3.4 g: 30-50 mL: 0.1-0.3 g.
4. The bending-resistant data line material according to claim 1, characterized in that: In step A3, the dosage ratio of KH-550, ethanol and MXene nanosheet aqueous solution is 0.5-1 g: 20 mL: 10 mL.
5. The bending-resistant data line material according to claim 4, characterized in that: The MXene nanosheet aqueous solution is prepared by the following steps: dispersing 3-6 g of Ti3AlC2 powder in 50-100 mL of 40% hydrofluoric acid, stirring for 12-24 h in a 30-40° C. water bath, filtering and washing until the filtrate is neutral, then drying the filter cake, and re-dispersing it in 10 mL of deionized water to obtain a MXene nanosheet aqueous solution.
6. The bending-resistant data line material according to claim 1, characterized in that: In step A4, the dosage ratio of halloysite nanotubes, polyvinyl alcohol, deionized water, silicone oil, sodium dodecyl sulfate, cross-linked product, hydrochloric acid, amino MXene nanosheet solution and sodium cyanoborohydride solution is 1.5-2.5 g: 3-5 g: 50 mL: 80-100 mL: 2-4 g: 0.5-1.5 g: 8-16 mL: 20 mL: 5 mL.
7. The bending-resistant data line material according to claim 6, characterized in that: The aminated MXene nanosheet solution is prepared by mixing and stirring aminated MXene nanosheets and deionized water in a dosage ratio of 0.2-0.6 g: 20 mL.
8. The bending-resistant data line material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010 and antioxidant 168.
9. A method for preparing the bending-resistant data line material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step S1, weighing raw materials by weight, adding SEBS, polypropylene, EPDM rubber and thermoplastic polyurethane elastomer into a mixer, stirring at a speed of 500-700 rpm, then adding composite flame retardant, white oil, antioxidant and stearic acid, stirring at a speed of 200-400 rpm for 30 minutes to obtain a mixture; Step S2, putting the mixed material into a twin-screw extruder, melting and extruding at 180-200° C., and granulating to obtain a bending-resistant data cable material.
Citation Information
Cited By
Mxene nano hybrid material and application thereof in flame-retardant foaming material
CN119978549A
Bending-resistant data line material and production process thereof
CN121045731A